Self-assembly of spherical and rod-shaped nanoparticles with full positional control. Issue 47 (22nd November 2019) - Lloyd, Julian A.; Liu, Yawei; Ng, Soon Hock; Thai, Thibaut; Gómez, Daniel E.; Widmer-Cooper, Asaph; Bach, Udo
Abstract : Fabricate nanoparticle dimers with a spherical particle either at the tip, the side or on top of a nanorod. Abstract : The controlled positioning of spherical gold nanoparticles and gold nanorods upon self-assembly on a substrate is of great interest for the fabrication of tailored plasmonic devices. Here, an electrostatic approach with a sequential two-step assembly protocol is presented as a cost-effective and high-yield alternative to previously presented, more complex proof of concepts. Three different geometries can be separately produced in large quantities relying on electrostatic attraction and repulsion of the charge-carrying building blocks: a single gold nanoparticle at the tip, the side or on top of a gold nanorod. DLVO theory is used to explain the electrostatic assembly strategy. The process is highly efficient and assembly yields between 79% (at the tip) and 94% (for the nanoparticle at the long side of the nanorod) are achieved.